Interim Steps on Quota and Governance Reform : Report of the Executive Board to the Board of Governors. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2015)
In light of continuing delays in the implementation of the 2010 quota and governance reforms (hereafter the '2010 Reforms'), the Board of Governors, in February 2015, adopted Resolution No. 70-1, which (i) expressed its deep regret that the quota increases under the Fourteenth General Review of Quotas (hereafter the 'Fourteenth Review') and the Proposed Amendment on the Reform of the Executive Board (hereafter the 'Board Reform Amendment') have not become effective, and that the Fifteenth General Review of Quotas (hereafter the 'Fifteenth Review') has not been completed; (ii) emphasized the importance and urgency of the 2010 Reforms for the Fund's credibility, legitimacy, and effectiveness, and reiterated its commitment to their earliest possible implementation; (iii) urged the remaining members who have not yet accepted the Fourteenth Review quota increases and the Board Reform Amendment to do so without further delay; (iv) called for the completion of the Fifteenth Review by December 15, 2015; and (v) called on the Executive Board to work expeditiously and to complete its work as soon as possible on interim steps in the key areas covered by the 2010 Reforms, pending their full implementation, and thus to enable the Board of Governors to reach agreement on steps that represent meaningful progress towards the objectives of the 2010 Reforms by June 30, 2015.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: United States